2009
DOI: 10.3341/kjo.2009.23.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab for the Treatment of Neovascular Glaucoma Associated With Central Retinal Artery Occlusion

Abstract: We report three cases of neovascular glaucoma secondary to central retinal artery occlusion (CRAO) which were effectively managed with intravitreal bevacizumab (IVB) followed by panretinal photocoagulation (PRP). Neovascular glaucoma without peripheral anterior synechiae developed between one and five weeks following CRAO onset. All patients received 0.75 mg (0.03 ml) IVB. In all patients, complete regression of the iris and anterior chamber angle neovascularization was confirmed within one week. PRP was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…They stated that the timing of all three patients developing NVG after the CRAO, in addition to the patients having no signs of ONV prior to the CRAO, strongly suggests an association between NVG and CRAO. In addition, their three patients had no delay in filling on fluorescein angiogram 9. More recently, in 2010, Rudkin et al stated that they demonstrated a clear correlation and a “causal relationship” between CRAO and NVI based on the timing of the two entities.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…They stated that the timing of all three patients developing NVG after the CRAO, in addition to the patients having no signs of ONV prior to the CRAO, strongly suggests an association between NVG and CRAO. In addition, their three patients had no delay in filling on fluorescein angiogram 9. More recently, in 2010, Rudkin et al stated that they demonstrated a clear correlation and a “causal relationship” between CRAO and NVI based on the timing of the two entities.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the detection of ONV following CRAO has ranged from as early as the day of presentation to 2 years after the CRAO diagnosis 4,8. With frequent visits, many cases of ONV can be managed early with treatments such as panretinal photocoagulation and off-label intravitreal bevacizumab 9,11,12. Rudkin et al concluded that since ONV can occur early, regular follow-up appointments should be required, especially within the first 4 months 5…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrated an incidence of NVI following acute CRAO of 10.9%. Previous studies have reported a prevalence of ocular NV post CRAO ranging from 3.0% to 28.2% [ 1 2 3 4 ]. Our result is within the range of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is estimated to be 1.80 in 100,000 people [ 1 ]. CRAO can induce neovascularization of the iris (NVI) and neovascular glaucoma (NVG), with a reported incidence of 1% to 20% [ 2 ]. Neovascularization (NV) of the iris is a relatively rare complication observed in the setting of retinal ischemic disease, including proliferative diabetic retinopathy (PDR), ocular ischemic syndrome (OIS), or central retinal vein occlusion (CRVO).…”
mentioning
confidence: 99%
“…13 Previous studies showed the success of intravitreally injected anti-VEGF molecule alone or in combination with panretinal laser for neovascularization regression. 14,15 Moreover, it is the first use of aflibercept with a single dose for treating the development of neovascularization after CRAO. To the best of our knowledge, this is the first report in the literature.…”
Section: Discussionmentioning
confidence: 99%